ATRAKTOR CUMI-CUMI : TEKNOLOGI POTENSIAL DAN TEPAT GUNA UNTUK PEMBERDAYAAN NELAYAN - Jamal, Muhammad (Jurnal BALIRESO, 2017)
Squid attractor in the watershas a role as an artificial reef, as a squid collector, and as a squidhabitat to lay their eggs. It is therefore, the settlement of the squid attractor in a waters region willcreate a unique underwater view, which are a layer of squid eggs bed. Additonally, the squidattractor can also to be a nursery habitat and at the endit can be developed to be a potencial fishingground.The problems are facing by partner groups (group Nelayan Mandiri and group NelayanSejahtera Bersama) are: 1) problems in production and 2) problems in business management. Forproducion problems they result in low production and influence the selling price linearly.Whereas, the poor business management will hamperthe production system and will reduce theprofit of fishermen group.The purpose of the program of the IbM kelompok nelayan cumi-cumi diKota Makassaris to provide counseling and demo to the partner groups in order to improve theirproductionand to increase their welfare. The approach methods applied in solving the agreedpriority problems of the partners duringthe realization of the program IbM program is to implemendemonstration system as well as counseling method. There are two selected partner groups,namelyNelayan MandiriGroup and Nelayan Sejahtera BersamaGroup.The group selection wasbased on purposive sampling by the facts that both groups have potential good product and market.From the 5 trips trial on the squid attractor, it was found the total catch of squid was in the range of10,8 â 11,2 kg on average.